2016
DOI: 10.1007/s13224-016-0910-2
|View full text |Cite
|
Sign up to set email alerts
|

Chaos

Abstract: The primary abnormality is an intrinsic obstruction of the upper airway. Normal lung development involves a continuous efflux of fluid from the fetal lungs. Laryngeal atresia/CHAOS stops the efflux of this fluid, and this retained fluid distends the alveoli with fluid giving the lungs voluminous echogenic appearance and inverting the diaphragm. Isolated airway obstruction without hydrops has a relatively favorable prognosis. CHAOS with associated anomalies and with early presentation of hydrops is an ominous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…As a result, fluid is trapped in the lungs, creating internal pressure which forces the lung to grow. This idea of blocking the airway emerged from an experiment of nature in patients with congenital high airway obstruction syndrome resulting in big polyalveolar lungs [50]. Previous research has shown that tracheal occlusion can indeed cause an increase in lung growth [51,52] and removing the balloon before birth has shown to be necessary for a better maturation of the lung by decreasing the apoptosis of the alveolar type 2 cells, which produce surfactant, an essential compound for lung function [53].…”
Section: Treatment Of Pulmonary Vascular Defects In Cdhmentioning
confidence: 99%
“…As a result, fluid is trapped in the lungs, creating internal pressure which forces the lung to grow. This idea of blocking the airway emerged from an experiment of nature in patients with congenital high airway obstruction syndrome resulting in big polyalveolar lungs [50]. Previous research has shown that tracheal occlusion can indeed cause an increase in lung growth [51,52] and removing the balloon before birth has shown to be necessary for a better maturation of the lung by decreasing the apoptosis of the alveolar type 2 cells, which produce surfactant, an essential compound for lung function [53].…”
Section: Treatment Of Pulmonary Vascular Defects In Cdhmentioning
confidence: 99%
“…Extrinsic compression can be caused by lymphatic malformations, vascular rings or masses such as teratomas. Intrinsic causes are mostly secondary to laryngeal atresia or tracheal atresia [ 1 ]. Embryologically, laryngeal atresia results from failure of recanalization of the larynx, whereas tracheal atresia results from unequal partitioning of the foregut into the esophagus and trachea [ 2 ]…”
Section: Discussionmentioning
confidence: 99%
“…These findings are pathognomonic for complete or near-complete obstruction of the fetal upper airway and carry a poor, often fatal prognosis. Etiologies of CHAOS include laryngeal or tracheal atresia, laryngeal or tracheal webs, laryngeal or tracheal agenesis, subglottic stenosis or atresia, congenital mass, and laryngeal cyst with laryngeal atresia representing the most frequent cause [ 2 ]. Embryologically, laryngeal atresia occurs due to failed recanalization of the vestibule and subglottic regions during the development of the larynx [ 3 ].…”
Section: Introductionmentioning
confidence: 99%